Reverse engineering of automotive piston - Arifutzzaman, A.; Maleque, Md. Abdul (2012)
To be aware of the present operating conditions of the automotive piston which are depended on the different mechanical and tribological properties, composition, microstructure and morphologies a comprehensive study of reverse engineering on an automotive piston is very essential. Therefore, the main aim of this work is to investigate and analyze a conventional automotive piston by performing the mechanical test, wear test, and microstructure analysis. A piston was destructed for the various experiments and investigations. Tensile test was performed using universal tensile testing (UTM) machine whereas hardness test was done on Vickers hardness tester. Microstructure and chemical analysis were performed using OM, EDX analyzer respectively. The wear test was performed using pin-on-disk (POD) machine. The tensile test results showed that the ultimate tensile strength and modulus of elasticity of the piston were 215 MPa and 73 GPa respectively, whereas the Vickers hardness number of this material was found to be 155 HV0.5kgf. The micrograph shows the phases of Si plate with ~17% of Si surrounded by α-Al matrix referring to the hypereutectic Al-Si alloy which was proven by the EDX analysis as well and the wear test results showed the moderate specific wear rate (with the range of 1.81 to 3.1 x10-6 mm3/N-m). The current RE analysis provides a guideline to replace or introduce a new material especially metal matrix composite for the application of new generation automotive piston with better properties, lighter weight and higher performance.